2003
DOI: 10.1242/jcs.00720
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of the cytoplasmic domain of β1,4-galactosyltransferase I: influence of phosphorylation on cell surface expression

Abstract: β1,4-Galactosyltransferase I (GalT I) exists in two subcellular compartments where it performs two distinct functions. The majority of GalT I is localized in the Golgi complex where it participates in glycoprotein biosynthesis; however, a small portion of GalT I is expressed on the cell surface where it functions as a matrix receptor by binding terminal N-acetylglucosamine residues on extracellular glycoside ligands. The GalT I polypeptide occurs in two alternate forms that differ only in the length of their c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 49 publications
(53 reference statements)
2
22
0
Order By: Relevance
“…Finally, glycosyltransferase phosphorylation has been described in vitro, but evidence for a functional consequence of this modification is currently lacking (Gallagher et al, 2001;Hathaway et al, 2003;Ma et al, 1999). The hypothesis most consistent with our results is that Sff modulates glycan processing by influencing the compartmentation of glycan processing within the Golgi apparatus.…”
Section: Tissue-specific Protein Glycosylation Requires Coordinated Tsupporting
confidence: 86%
“…Finally, glycosyltransferase phosphorylation has been described in vitro, but evidence for a functional consequence of this modification is currently lacking (Gallagher et al, 2001;Hathaway et al, 2003;Ma et al, 1999). The hypothesis most consistent with our results is that Sff modulates glycan processing by influencing the compartmentation of glycan processing within the Golgi apparatus.…”
Section: Tissue-specific Protein Glycosylation Requires Coordinated Tsupporting
confidence: 86%
“…Several studies have reported alterations in lipid raft composition during sperm capacitation that are thought to be a prerequisite for sperm binding to the egg coat (Cross, 2004;Bou Khalil et al, 2006). GalT1 has been shown to locate to lipid rafts in somatic cells (Hathaway et al, 2003), although it is still unclear whether GalT1 is present within lipid rafts on sperm as well. If so, then the loss of GalT1 might disrupt or alter the presentation of the EBM components within the lipid raft, leading to reduced affinity for egg coat ligands, including ZP3 and OGP.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that GalT1-associated GTAP may instead affect the internalization of cell surface GalT1 through ubiquitination of surrounding membrane proteins in coated pits or caveolae. Partial support for this hypothesis is that a small fraction of cell surface GalT1 has been cofractionated with caveolin in lipid rafts [21]. Furthermore, long GalT1 has been shown to associate with Src-suppressed C kinase substrate (SSeCKS), a previously defined kinase and cytoskeleton scaffolding protein important for agonist-induced internalization and resensitization of G-protein-linked receptors [20,35].…”
Section: Discussionmentioning
confidence: 99%
“…A HindIII/SacI fragment containing the gene of interest was then ligated into the multiple cloning site of pAcGFP1-C2 expression vector (BD Biosciences). Expression vectors harboring cDNA coding for GFP fusion proteins of GalT1 long and short cytoplasmic domains, GFP-24-amino-acid-long cytoplasmic domain (LCD 24 ) and GFP-SCD 11 were produced, as previously described [21].…”
Section: Gtap Cdna Cloning Recombinant Protein Preparation and Cdnamentioning
confidence: 99%